Dual Targeting of BRAF and mTOR Signaling in Melanoma Cells with Pyridinyl Imidazole Compounds - Palušová, Veronika; Renzová, Tereza; Verlande, Amandine; Vaclová, Tereza; Medková, Michaela; Cetlová, Linda; Sedláčková, Miroslava; Hříbková, Hana; Slaninová, Iva; Krutá, Miriama; Rotrekl, Vladimír; Uhlířová, Hana; et al. (Cancers, 2020)
BRAF inhibitors can delay the progression of metastatic melanoma, but resistance usually emerges, leading to relapse. Drugs simultaneously targeting two or more pathways essential for cancer growth could slow or prevent the development of resistant clones. Here, we identified pyridinyl imidazole compounds SB202190, SB203580, and SB590885 as dual inhibitors of critical proliferative pathways in human melanoma cells bearing the V600E activating mutation of BRAF kinase. We found that the drugs simultaneously disrupt the BRAF V600E-driven extracellular signal-regulated kinase (ERK) mitogen-activated protein kinase (MAPK) activity and the mechanistic target of rapamycin complex 1 (mTORC1) signaling in melanoma cells. Pyridinyl imidazole compounds directly inhibit BRAF V600E kinase. Moreover, they interfere with the endolysosomal compartment, promoting the accumulation of large acidic vacuole-like vesicles and dynamic changes in mTOR signaling. A transient increase in mTORC1 activity is followed by the enrichment of the Ragulator complex protein p18/LAMTOR1 at contact sites of large vesicles and delocalization of mTOR from the lysosomes. The induced disruption of the endolysosomal pathway not only disrupts mTORC1 signaling, but also renders melanoma cells sensitive to endoplasmic reticulum (ER) stress. Our findings identify new activities of pharmacologically relevant small molecule compounds and provide a biological rationale for the development of anti-melanoma therapeutics based on the pyridinyl imidazole core.
Keywords: BRAF V600E; melanoma; mTORC1; endosome; ER stress; pyridinyl imidazole; lysosome; small molecule drug; BRAF inhibitor